ANALISIS MODAL KERJA DAN PERPUTARAN MODAL KERJA TERHADAP RETURN ON ASSETS PADA PERUSAHAAN SEKTOR INDUSTRI KIMIA DI BURSA EFEK INDONESIA - Rio Rahmat Yusran (Bajang Institute, 2021)
This study aims to analyze working capital and working capital turnover on return on assets in chemical companies listed on the Indonesia Stock Exchange (IDX) for the period 2016 to 2020. The research method used is quantitative method, and uses multiple linear regression analysis. technique with SPSS application program. The results of this study partially show that working capital has a positive and significant effect on return on assets (ROA) with a tcount value (2.247) > t table (2.048), and working capital turnover has a positive and significant effect. effect on return on assets (ROA) with t count (2.414) > t table (2.048). the results of the f test or simultaneously indicate that working capital and working capital turnover have a positive effect on return on assets (ROA), with the value of F-count (3,836) > F-table (3,354). The value of R Square in this study is 0.221, or 22.1%. This shows the remaining 77.9% is influenced by other variables outside the study.